TRANSPORT BEHAVIOR OF Cr(III), Cd(II), Pb(II), AND Ag(I) IONS THROUGH BULK LIQUID MEMBRANE CONTAINING p-tert-BUTYLCALIX[4]ARENE–TETRADIETHYLACETAMIDE AS ION CARRIER - Maming Maming; Jumina Jumina; Dwi Siswanta; Hardjono Sastrohamidjojo; Keisuke Ohto (Universitas Gadjah Mada, 2008)
The study on the transport behavior of Cr(III), Cd(II), Pb(II), and Ag(I) through bulk liquid membrane using p-tert-butylcalix[4]arene-tetradiethylacetamide as ions carrier has been conducted. The aims of this work are to determine the optimum condition, efficiency, and transport selectivity of the carriers for those ions. Both optimum condition and transport efficiency were obtained by determination of the concentration of transported ions with variation of the source phase pH, ion carrier concentration, the nature of decomplexant agent in the receiving phase, and transport time. The transport selectivity of the ion carrier was obtained from the ions competition transport experiments. The amount of Cr(III), Pb(II), Cd(II), and Ag(I) transported across liquid membrane were 11.6, 25.5, 39.5, and 42.1% respectively. The ion carrier is selective for Cd(II), Pb(II), Ag(I), and strongly depends on the nature of decomplexant agent as well as transport mechanism. The remarkable selectivity was shown by the ion carrier to Ag(I) when the transport process was carry out under high concentration of acid in the source phase.